THE INFLUENCE OF OXYGEN CLASSES ON THE LEVELS OF FLEXIBILITY AND BALANCE OF OLDER ADULTS (Fiep Bulletin - online, 2011)
The number of older adults joining in training programs aimed at this population has increased significantly, so the importance of emphasizing the prescription and supervision of activities. The aim of this study was to examine whether the Oxygen physical training program has some influence on flexibility and balance in older people. The sample consisted of 10 individuals of both sexes, 60 to 80 years-old, chosen randomly. First, they had their heights and weights measured, then their flexibility was assess through the flexitest, that measures 8 joints and movements. The balance was assessed through the Berg balance Scale, which consists of 14 questions with maximum score of 56 points. Then, subjects underwent a 8-week- training of Oxygen, three times a week, after which the post-test was conducted to obtain their results. For statistical analysis we used the nonparametric Wilcoxon test, with significance of p ≤ 0.05. This study had an attrition rate of 60% of the elderly, finishing with only four subjects. As noted in this study, Oxygen training showed a tendency toward increasing flexibility and balance in older people, but not significant.
Keywords: flexibility; balance; gymnastics